Vitamin B12 deficiency in a young male with Imerslund-Gräsbeck syndrome: case report - Xing, Lina; Guo, Yujie; Li, Yang; Zhou, Xuquan; Lin, Fengru; Wang, Yan (Frontiers in Pediatrics, 2025)
Imerslund-Gräsbeck syndrome (IGS) is a rare genetic disorder characterized by selective vitamin B12 deficiency co-existing with asymptomatic proteinuria. It is caused by bi-allelic mutations in either the CUBN or AMN gene, which encode the two protein components of the cobalamin-intrinsic factor receptor. Patients stay healthy with lifelong parenteral administration of vitamin B12. Here, we report a case of a young male who presented with severe macrocytic anemia and asymptomatic proteinuria from the age of one year. His low serum level of vitamin B12 suggested vitamin B12 deficiency. Further, the patient was heterozygous for the AMN variant c.1006 + 34_1007-31 del mutation with duplication of exons 2–3, indicating a definite diagnosis of typical IGS. He was treated by administration of vitamin B12 injections, resulting in rapid improvement of hemoglobin levels. However, the previously detected proteinuria was found to persist at follow-up.